2006
DOI: 10.1373/clinchem.2006.072397
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Assay for the Detection and Mapping of Complex Glycerol Kinase Deficiency

Abstract: Background: Glycerol kinase deficiency (GKD) is an X-linked recessive disorder that presents in both isolated and complex forms. The contiguous deletion that leads to GKD also commonly affects NR0B1 (DAX1), the gene associated with adrenal hypoplasia congenita, and DMD, the Duchenne muscular dystrophy gene. Molecular testing to delineate this deletion is expensive and has only limited availability. Methods: We designed a multiplex PCR assay for the detection and mapping of a contiguous deletion potentially aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Among these, IL1RAPL1 (interleukin-1 receptor accessory protein-like 1) was first described and mapped to Xp22.1-Xp21.3 in 1999 [Carrie et al, 1999]. It is located distal to DMD (dystrophin), GK (glycerol kinase), and DAX-1 (NR0B1, nuclear receptor subfamily 0, group B, member 1) and proximal to ARX (aristaless-related homeobox), and has been found to be deleted together with a variable number of adjacent genes in numerous patients with a contiguous gene syndrome [Carrie et al, 1999;Jin et al, 2000;Sasaki et al, 2003;Wheway et al, 2003;Zhang et al, 2004;Klein et al, 2006]. So far, three point mutations of IL1RAPL1 [Carrie et al, 1999;Tabolacci et al, 2006;Piton et al, 2008] and different cytogenetic aberrations involving IL1RAPL1 [Laumonnier et al, 2002;Lepretre et al, 2003;Bhat et al, 2008] have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, IL1RAPL1 (interleukin-1 receptor accessory protein-like 1) was first described and mapped to Xp22.1-Xp21.3 in 1999 [Carrie et al, 1999]. It is located distal to DMD (dystrophin), GK (glycerol kinase), and DAX-1 (NR0B1, nuclear receptor subfamily 0, group B, member 1) and proximal to ARX (aristaless-related homeobox), and has been found to be deleted together with a variable number of adjacent genes in numerous patients with a contiguous gene syndrome [Carrie et al, 1999;Jin et al, 2000;Sasaki et al, 2003;Wheway et al, 2003;Zhang et al, 2004;Klein et al, 2006]. So far, three point mutations of IL1RAPL1 [Carrie et al, 1999;Tabolacci et al, 2006;Piton et al, 2008] and different cytogenetic aberrations involving IL1RAPL1 [Laumonnier et al, 2002;Lepretre et al, 2003;Bhat et al, 2008] have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…CGKD is now recognized as a microdeletion syndrome involving not only the GK locus, but also DAX1 and/or DMD loci in the Xp 21.3 region [1,6]. A range of genotypes and phenotypes can occur in CGKD, which vary from asymptomatic "hyperglycerolemia" to lifethreatening metabolic crises.…”
Section: Discussionmentioning
confidence: 99%
“…DMD is a progressive muscle disease resulting from the absence of the muscle protein dystrophin in dystrophin gene deletion [1,8]. DMD patients appear normal until they start walking, then they begin to experience difficulties in activities.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that both dystrophin and IL1RAPL1 genes are present in the same common fragile site (FRAXC), 10 it is reasonable to consider co-occurrence of mutations in these two genes [11][12][13] Production of a chimeric dystrophin-IL1RAPL1 transcript, however, has been shown in one DMD patient who had a deletion encompassing B1.6 Mb from the IL1RAPL1 gene to the dystrophin gene. 12 Our case is the second to show the production of a chimeric dystrophin-IL1RAPL1 transcript (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…10 However, little attention has been paid to IL1RAPL1 gene mutation in dystrophinopathy, even though mental retardation is observed in nearly one-third of DMD patients. The co-occurrence of mutations in these two genes has been reported in a contiguous gene deletion syndrome, in which both dystrophin and IL1RAPL1 genes are affected, the deletion beginning and ending within these genes [11][12][13] Therefore, it is supposed that an unknown mechanism mutates these two separated genes concurrently. Recently, a mechanism of the fork stalling and template switching (FoSTeS) was proposed as a novel mechanism to mutate two separated genes.…”
Section: Introductionmentioning
confidence: 99%